TANGGUNG JAWAB PERUSAHAAN JASA PENGIRIMAN BARANG TERHADAP KERUSAKAN BARANG (STUDI PADA PT. DAKOTA BUANA SEMESTA CABANG BANDA ACEH) - Nurfahlita Dewi Rambe; Hasim Purba; Dedi Harianto (Smart Education, 2025)
Abstract: Land delivery services have an important role in the distribution of goods and support national economic development. Delivery of goods is carried out based on an agreement between the sender and the service provider, but damage to goods often occurs due to negligence of the delivery service, so legal protection is needed in accordance with Law Number 8 of 1999 concerning Consumer Protection, the Civil Code, the Commercial Code, and Law Number 22 of 2009 concerning Road Traffic and Transportation. This study aims to analyze the regulation of PT. Dakota Buana Semesta Banda Aceh Branch's liability in the event of damage to goods during the delivery process, limitations of liability, and legal protection for the sender of goods to demand responsibility if there is damage to goods during the delivery process. The method used in this thesis is normative juridical research supported by field research or prescriptive analysis. The results of the study indicate that the company's liability is based on the delivery agreement as regulated in the Civil Code, the Commercial Code, Law Number 8 of 1999 concerning Consumer Protection, and Law Number 22 of 2009 concerning Road Traffic and Transportation. Limitations of liability apply to high-value, uninsured goods and those affected by force majeure. While legal protections offered to shippers include preventive and repressive measures, they still face challenges in claims procedures, reporting deadlines, and compensation amounts. Keyword: Legal Liability, Damage to Goods, Delivery of Goods Abstrak: Jasa pengiriman darat memiliki peranan penting dalam distribusi barang dan mendukung pembangunan ekonomi nasional. Pengiriman barang dilakukan berdasarkan perjanjian antara pengirim dan penyedia jasa, namun kerusakan barang kerap terjadi akibat kelalaian pihak jasa pengiriman, sehingga diperlukan perlindungan hukum sesuai dengan Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen, KUHPerdata, KUHD, serta Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan. Penelitian ini bertujuan untuk menganalisis pengaturan pertanggungjawaban PT. Dakota Buana Semesta Cabang Banda Aceh dalam hal terdapat kerusakan barang dalam proses pengiriman, pembatasan pertanggungjawaban, serta perlindungan hukum pengirim barang untuk meminta pertanggungjawaban apabila terdapat kerusakan barang dalam proses pengiriman. Metode yang digunakan dalam tesis ini adalah penelitian yuridis normatif didukung dengan penelitian lapangan atau preskriptif analisis. Hasil penelitian menunjukkan bahwa tanggung jawab perusahaan didasarkan pada perjanjian pengiriman sebagaimana diatur dalam KUHPerdata, KUHD, Undang- Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen, dan Undang-Undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan. Pembatasan tanggung jawab diberlakukan untuk barang bernilai tinggi yang tidak diasuransikan dan dalam keadaan force majeure. Perlindungan hukum yang diberikan kepada pengirim mencakup perlindungan preventif dan represif, namun masih menghadapi kendala dalam prosedur klaim, batas waktu pelaporan, dan nominal ganti rugi. Kata kunci: Pertanggungjawaban Hukum, Kerusakan Barang, Pengiriman Barang